Nitride formation during reactive sputter deposition of multi-principal element alloys in argon/nitrogen mixtures - Depla, Diederik; Dedoncker, Robin; Strijckmans, Koen (Thin solid films, 2021)
•Reactive sputtering of nitrides based on multi-principal element alloys.•Film texture of low reactivity materials is defined by the sputtered nitrogen.•Correlation between target reactivity and average electronegativity. Nitrides based on multi-principal element alloys have been deposited by reactive magnetron sputtering from powder targets. All deposited nitrides were based on alloys of which the majority of the constituent metals have a low chemical affinity to molecular nitrogen (Co, Cu, Fe, Ni, Mn, and Zn). Some more reactive metals (Al, Cr, Ti, Mo, and V) were also added. The nitrogen incorporation in these alloys was investigated based on two different approaches. The incorporation efficiency is calculated based on the chemical composition of the deposited layer, and the metal flux towards the substrate. The calculations are based on a previous published model to simulate the reactive magnetron sputtering process. The observed trends are compared with results obtained from (energy resolved) mass spectrometry measurements. Both methods proof that the nitrogen incorporation is dominated by sputtered nitrogen from the (partially) poisoned target. The composition weighted electronegativity average of the alloy constituent elements is used to asses the target poisoning level. It is shown that this electronegativity average correlates with the incorporation efficiency. The nitrogen incorporated in these alloys is mainly atomic nitrogen which affects the texture development. In contrast to nitrides based on highly reactive metals such as Ti which exhibit a cubic 〈111〉 fiber texture, a cubic 〈001〉 fiber texture is observed for the studied alloys.